2011
DOI: 10.1111/j.1365-313x.2011.04532.x
|View full text |Cite
|
Sign up to set email alerts
|

Over‐expression of PHO1 in Arabidopsis leaves reveals its role in mediating phosphate efflux

Abstract: SUMMARYInorganic phosphate (Pi) homeostasis in multi-cellular eukaryotes depends not only on Pi influx into cells, but also on Pi efflux. Examples in plants for which Pi efflux is crucial are transfer of Pi into the xylem of roots and release of Pi at the peri-arbuscular interface of mycorrhizal roots. Despite its importance, no protein has been identified that specifically mediates phosphate efflux either in animals or plants. The Arabidopsis thaliana PHO1 gene is expressed in roots, and was previously shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 49 publications
8
88
0
Order By: Relevance
“…It was previously demonstrated that overexpression of PHO1 in leaves using the native promoter led to an increase in export of Pi into the xylem vessel and consequently out of the leaves, revealing a role for PHO1 in mediating Pi efflux (Stefanovic et al, 2011). In contrast with the drastic effect of PHO1 accumulation in leaves, overexpression of PHO1 in roots was only associated with a minor change in the rate of root-to-shoot Pi translocation.…”
Section: Mode Of Action Of Pho1 In Mediating Pi Transfer Into the Roomentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously demonstrated that overexpression of PHO1 in leaves using the native promoter led to an increase in export of Pi into the xylem vessel and consequently out of the leaves, revealing a role for PHO1 in mediating Pi efflux (Stefanovic et al, 2011). In contrast with the drastic effect of PHO1 accumulation in leaves, overexpression of PHO1 in roots was only associated with a minor change in the rate of root-to-shoot Pi translocation.…”
Section: Mode Of Action Of Pho1 In Mediating Pi Transfer Into the Roomentioning
confidence: 99%
“…In contrast with the drastic effect of PHO1 accumulation in leaves, overexpression of PHO1 in roots was only associated with a minor change in the rate of root-to-shoot Pi translocation. In this regard, Stefanovic et al (2011) surmised that other factors limiting Pi efflux activity, such as the rate of Pi transfer across the endodermis, or mechanisms of posttranslational control of PHO1 activity present in roots but absent in shoots may explain the different effects of PHO1 when expressed in these two different tissues. The latter speculation is in agreement with the observations of predominant expression of PHO2 in the root and PHO2-dependent degradation of PHO1 shown here.…”
Section: Mode Of Action Of Pho1 In Mediating Pi Transfer Into the Roomentioning
confidence: 99%
“…Among the six members of the PHT4 family, one is located in the Golgi membrane and five are found in the plast envelope (Guo et al, 2008). Another key component, PHO1, was identified in a genetic screen searching for low shoot Pi content, as pho1 mutation impaired xylem loading of Pi (Poirier et al, 1991) and it appears to be involved in Pi efflux (Stefanovic et al, 2011). Additional phosphate carriers have also been reported in the plastidic membrane, where they couple the exchange between phosphorylated metabolites and Pi (Rausch and Bucher, 2002).…”
Section: Pi Uptake Activity Relies On Pht1 Transportersmentioning
confidence: 99%
“…The PHO1 protein, primarily expressed in the root vascular cylinder, is known for mediating Pi efflux in loading Pi to root xylem in Arabidopsis (Hamburger et al, 2002;Stefanovic et al, 2011). In rice, it has been shown that OsPHO1;2 plays an important role in transferring Pi from roots to shoots (Secco et al, 2010).…”
Section: Ospt1 Functions In Pi Acquisition and Distribution And Pi-mementioning
confidence: 99%